2017
DOI: 10.1002/joc.5064
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation modelling using different machine learning techniques

Abstract: Accurate prediction of pan evaporation (Ep) is critical for water resource management. This article investigates the capabilities of three different soft computing methods at estimating monthly Ep at six stations in the Yangtze River Basin using climatic factors, including the air temperature (Ta), solar radiation (Rg), air pressure (Pa) and wind speed (Ws) for the period of 1961–2000. The first part of the study focused on testing and comparing model accuracy levels at each station using local input combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 47 publications
(71 reference statements)
1
25
0
1
Order By: Relevance
“…Results proved the high ability of the FG model in pan evaporation estimation. Wang, Kisi, Hu, et al (2017) predicted pan evaporation using MLPNN, GRNN, ANFIS with grid partition (ANFIS-GP), MARS, MLR, FG, LSSVM, and SS models in China. The results showed that the AI models provided the most accuracy than the SS and MLR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Results proved the high ability of the FG model in pan evaporation estimation. Wang, Kisi, Hu, et al (2017) predicted pan evaporation using MLPNN, GRNN, ANFIS with grid partition (ANFIS-GP), MARS, MLR, FG, LSSVM, and SS models in China. The results showed that the AI models provided the most accuracy than the SS and MLR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These authors have, for other regions, estimated evapotranspiration from the same meteorological data required by the Penman-Monteith, as well as from scarce data. Methods such as neural networks, regression trees, support vector machines and many others present, for the most part, a heuristic characteristic coupled with a high ability to generalize and model patterns (Wang et al, 2017b(Wang et al, , 2017c.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, GA is an oversimplification of biological evolution [51]. GP, introduced by [52,53], solves the problem of fixed length solutions (as stated for GA) by creating nonlinear entities. Each entity (parse tree) has a distinguished shape and size.…”
Section: Methodsmentioning
confidence: 99%